Perspectives on regional science in studies of public participation in higher education - N. V. Vlasova; E. I. Molokova; E. S. Kulikova (Модернизация, инновация, развитие, 2023)
Purpose: of this paper is to characterize the potential of regional theories in solving the current scientific socio-economic problem of establishing the interaction between society and the system of higher education.Methods: the processes of interaction between society and higher education are considered through the prism of separate approaches and concepts of the scientific paradigm of regional economics, to solve the set goal.Results: based on statistical data, significant regional differentiation of higher education system in modern Russia is shown, which actualizes its study through the prism of regional scientific paradigm. Through systematization of existing experience of interaction between universities and society in Sverdlovsk region the role of universities as coordinators of public participation in the spatial development of the region is shown. By applying methodological apparatus of specific theories of regional paradigm, their cognitive potential in the sphere of educational social relations analysis as well as possibilities of identification of problems of public participation in higher education are revealed.  In particular, the gnoseological possibilities of the spatial approach are substantiated. The characteristics of the last reform of higher education, which entailed the segregation of universities in the context of applying the theory of growth poles, are given. The article shows the prospects for regional development through the application of the methodology of the theory "center–periphery", usingthe example of correcting staff imbalances of the small towns. The practical significance of applying the theory of "genetic" codes in the study and interpretation of the causes of low intensity and quality of public participation in higher education was characterized. The methodological possibilities of using institutional mesoeconomics, coordination theory, mesoeconomics of network structures, and cluster theory in studying the experience of interaction between higher education institutions and society in the regional context were substantiated.Conclusions and Relevance: the interpretation of the region in the context of mesoeconomics stipulates the necessity and possibility to form an independent theoretical and methodological apparatus for studying regional systems of higher education and apply special tools for analysis and identification of problems of public participation in higher education on specific territories.